Students’ nutritional status at Thach Ban High School (Hanoi) and Tien Lu High School (Hung Yen) in 2024 - 2025 - My, Do Tra; Truc, Le Thi Thanh; Quynh, Luu Thi Nhu; Tham, Nguyen Thi Hong; Thao, Nguyen Thi; Yen, Nguyen Ha; Lan, Nguyen Thi Huong (Tạp chí Nghiên cứu Y học, 2026)
This cross-sectional descriptive study assessed the nutritional status of 259 students from Thach Ban High School (Hanoi) and Tien Lu High School (Hung Yen) during the 2024 - 2025 academic year. Nutritional status was classified according to WHO 2006 standards, and data were analyzed using Jamovi with Fisher’s Exact Test. The prevalence of overweight was significantly higher among students at Thach Ban than at Tien Lu (26.61% vs. 11.11%, p = 0.001), while obesity rates did not differ significantly between the two schools (p = 0.532). A significantly greater proportion of students with normal nutritional status was observed at Tien Lu (p = 0.038). Male students showed a higher prevalence of overweight (p = 0.015), whereas female students were more likely to have normal nutritional status (p = 0.002). No statistically significant difference was found between groups in terms of stunting or thinness (p > 0.05). Overall, the findings indicate a double burden of malnutrition among high school students, with disparities by region and gender.